Pendampingan Penerapan Prinsip Fisika Bangunan Skala Mikro untuk Menciptakan Lingkungan Rumah Sehat di Kelurahan Sambiroto - Fatikasari, Tanty; Al Adawiyah, Novia (CV. Aksara Global Akademia, 2026)
Dense urban settlements often leave limited space between buildings, reducing natural ventilation and daylight inside houses. These conditions may increase indoor humidity, reduce occupants' comfort, and accelerate the deterioration of several building components. This community service program aimed to improve public understanding of building physics principles through micro-scale mentoring focused on natural ventilation, daylighting, and moisture control. The program was conducted in Sambiroto, Semarang, involving five housewives and one local construction worker. Activities consisted of participatory discussions supported by visual learning materials followed by on-site consultation during a house renovation project. Participants' understanding was evaluated using a five-point Descriptive Achievement Scale. The results showed that all participants achieved a very good category in thermal comfort and moisture control. The mentoring activities also led to the implementation of practical recommendations, including the use of a vertical void above the staircase to promote the stack effect and the installation of an aluminium foil layer beneath the roof covering to reduce heat transfer into the building. These findings suggest that direct field-based mentoring can effectively support communities in understanding and applying building physics principles to create healthier, more comfortable, and energy-efficient housing